2021
DOI: 10.1002/jmrs.535
|View full text |Cite
|
Sign up to set email alerts
|

0° vs. 180° CT localiser: The effect of vertical off‐centring, phantom positioning and tube voltage on dose optimisation in multidetector computed tomography

Abstract: Introduction: Patient positioning is an essential consideration for the optimisation of radiation dose during CT examinations. The study objectives seek to explore the effects of vertical off-centring, localiser direction (0°and 180°), and phantom positioning (supine and prone) on radiation dose, using three different tube voltages in multidetector computed tomography (MDCT) imaging. Methods: The trunk of a PBU-60 anthropomorphic phantom was imaged using a Discovery CT750 HD -128 slice (GE Healthcare). Images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…We barely saw patients being positioned above the iso-centre (29/684, 4%). This is in line with previously published articles [12]. Interestingly, in a study of Ryu et al, off-centreing has no clinical impact on radiation dose in the routine clinical practice [16].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We barely saw patients being positioned above the iso-centre (29/684, 4%). This is in line with previously published articles [12]. Interestingly, in a study of Ryu et al, off-centreing has no clinical impact on radiation dose in the routine clinical practice [16].…”
Section: Discussionsupporting
confidence: 89%
“…The effect is well described in literature. Al-Hayek et al and Paolicchi et al even noticed that the magnification effect was more pronounced for 180 • -localisers, compared to 0 • -localisers [12,13]. Kaasalainen et al evaluated the effect of phantom positioning in chest CTs.…”
Section: Discussionmentioning
confidence: 99%
“…That explains why the cross-over of the CTDIv is located at a point above the system's iso-center as shown in Figure 6a. It also explains why using a PA localizer has a higher CTDIv than that of using an AP localizer when patients are positioned at the iso-center [12][13][14][15][16], because the iso-center I is at a magnifying position in the PA projection according to O. This mismatch could be avoided if manufacturers use both AP and PA projections to define the projection center for the ATCM.…”
Section: Discussionmentioning
confidence: 99%
“…ATCM takes the reduced photon flux through the body of a patient as a thicker body, and therefore applies a higher tube current. As a result, PA localizer has a higher CTDIv than that of an AP localizer in ATCM [12][13][14][15][16]. The American Association of Physicists in Medicine (AAPM) recommends AP and LAT projection images be used for the calculations of body sizes [10].…”
Section: Introductionmentioning
confidence: 99%
“…The study reported here represents a further analysis of data collected as a part of a larger study, which details the experiment and dose measurements [ 20 ]. The trunk of a PBU-60 anthropomorphic phantom (Kyoto Kagaku Co., Ltd., Kyoto, Japan) representing an average-sized adult was scanned using a 128-slice MDCT system (Discovery CT750 HD, GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%